(untitled) (Research, Society and Development, 2019)
Tourism is an economic activity that aims to promote the conservation of natural resources and the social development of a community, by means of peculiar features, such as the nature, history and geological features. Thereby, this work aimed to characterize, by means of the observation and analysis of satellite images, the rock types and geological structures on eight trails in the Serra dos Alves’s region, Senhora do Carmo district, Itabira (MG), and to highlight the tourist modalities that could be developed from the local characteristics. It was observed rocks belong to the Espinhaço Supergroup, represented by quartzites and metaconglomerate, besides metabasic rocks correlated to the Pedro Lessa Suite. Under the structural perspective, there is the east-west orientation of fractures plans, responsible for the formation of tourist attractions. It was generally noted that the region presents potential for the development of ecotourism, adventure tourism and geotourism, but it is important to institute public policies, ensuring the preservation of the cultural identity of the community, as well as environmental conservation.